Optimized Design and Development of a Bioresorbable High Rotational Stability Fixation System for Small Bone Fragments. Issue 5 (6th March 2020) - Cingolani, Alberto; Casalini, Tommaso; Binelli, Marco Riccardo; Cignoli, Eleonora; Di Gialluca, Lorenza; Zambon, Fabio; Villa, Tomaso; Grottoli, Carlo Francesco; Klaue, Kaj; Rossi, Filippo; Perale, Giuseppe
Abstract : Bioresorbable pins are experiencing a growing interest and a likewise increasing use in orthopedic surgery for bone fixation. Indeed, such devices are naturally degraded by the human body and a subsequent surgery for their removal is not needed. However, bioresorption has a remarkable side effect on the performance of the devices, since mechanical properties decay over time. This aspect is essential for bone healing. In the first 60 days, the pin must bear continuous mechanical stress while preventing torsional slip of bone fragments. Although torsional support can be improved with suitable pin section design, degradation kinetics and the consequent loss in mechanical stability are slowed down while using high molecular weight polymers, whose slow bioresorption increases recovery time and negatively affects patient care. Herein, a bioresorbable pin of new conception, in terms of cross‐sectional shape and material formulation, is presented. Both section and polymer design are optimized through comprehensive mathematical modeling, which synergistically combines degradation and mechanical loads. As a result of the model, bioresorption time is minimized, whereas adequate mechanical resistance is ensured for the first 60 days. The most promising device is then injection molded, sterilized, mechanically tested, and successfully evaluated ex vivo in human femoral heads. Abstract : An optimized pin for the treatment of small fractures is obtained via mathematical modeling, identifying the most favorable cross‐section shape and polymer composition. This way, it is possible to ensure appropriate fixation and tuned resorption time, without loss of mechanical properties. The devices are injection molded, sterilized, and successfully evaluated ex vivo in human femoral heads.